FUNDAMENTAL AND CLINICAL STUDIES ON BRL 28500 (CLAVULANIC ACID-TICARCILLIN) IN THE FIELD OF PLASTIC AND RECONSTRUCTIVE SURGERY - HOMMA, KEN-ICHI; SUGANO, HIROYUKI; HONDA, KOUICHI; YOSHIDA, TETSUNORI; OHURA, TAKEHIKO (CHEMOTHERAPY, 1986)
BRL 28500, a formulation of the antimicrobial agent ticarcillin (TIPC) and the β-lactamase inhibitor clavulanic acid (CVA), was evaluated to establish its distribution to the skin, antibacterial activity and clinical effect. Following intravenous administration of BRL 28500 1.6g to patients who were about to be subject to full thickness skin grafts under general anesthesia, TIPC and CVA showed high serum and skin concentration levels. The maximum level of TIPC and CVA in the serum was observed 30 minutes after injection, the value was 109.58μg/ml and 5.44μg/ml respectively. However the maximun level in the skin was observed 1 hour after injection, TIPC value was 20.60μg/g and CVA value was 1.30μg/g. The ratio of the skin level to the serum concentration 1 hour after administration was 29%(20.60/70.79) for TIPC and 39%(1.30/3.33) for CVA. The antibacterial activity of BRL 28500 against 106 clinical isolates of Staphylococcus aureus was 2 tubes superior to TIPC and 2 to 4 tubes superior to piperacillin. In clinical studies, BRL 28500 was administered at a dose of 3.2g to 6.4g per day for 4 to 21 days to 16 patients with skin infections. The clinical effect of BRL 28500 was excellent in 2, good in 13 and poor in 1 case. No adverse reactions were observed and in laboratory findings, only one patient who had a history of liver insufficiency, showed a tentative elevation of S-GOT, S-GPT and total bilirubin level.